2022
DOI: 10.1088/2053-1591/ac6fba
|View full text |Cite
|
Sign up to set email alerts
|

State of the art review on the sustainable dry machining of advanced materials for multifaceted engineering applications: progressive advancements and directions for future prospects

Abstract: In this article, the comprehensive review on the application, and indeed, a comparative analysis on dry machining of different types of materials (Inconel, steel, aluminum, cast iron, magnesium and advanced materials) used in machining (turning, drilling and milling operations) were carried out in the light of utmost works published in the literature. The work describes the scientific findings of the past twenty years, including sustainable methods (surface texture, solid lubricants, vibration-assisted machini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…However, friction due to sliding and rotary motion of chip has created the abrasion marks on the top surface of cutting tool where the lubricant media is not accessible due to high sliding velocity and lower cutting area. Hence, dual lubrication nozzle should be the good option for to reduce the same [ [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
“…However, friction due to sliding and rotary motion of chip has created the abrasion marks on the top surface of cutting tool where the lubricant media is not accessible due to high sliding velocity and lower cutting area. Hence, dual lubrication nozzle should be the good option for to reduce the same [ [82] , [83] , [84] ].…”
Section: Resultsmentioning
confidence: 99%
“…The tool holder used for holding the tool is PSBNL 25 25 M12. Singh et al (12) determined from their study that PVD coated (TiAlN) is best suited for dry machining. TH 1000 is a PVD coated tool with a Ti-Al-Si-N nanolaminate coating.…”
Section: Tool Materialsmentioning
confidence: 99%
“…From Figure 3 (i) it can be concluded that "P c " was higher for 80 m/min for all "DoC" when compared to other "V c ". Singh et al (12) concluded from their review that dry machining showed promising results and reduced the excess cost that comes with the usage of cutting fluid, employing coating technology is the best scope for dry machining and PVD coated (TiAlN) is best suited for dry machining. In agreement with the current study, Emrah Şahin et al (14) , Raman Kumar et al (15) , Sivaiah et al (16) , Rajarajan et al (17) and Sarvam Patel et al (18) have concluded from their studies that "R a " decreases with the increase in cutting speed, and an increase in feed leads to an increase in "R a ".…”
Section: Fig 2 (A) Main Effect Plot For Means Of Mean For Surface Rou...mentioning
confidence: 99%
“…RHVT MF strategy reduces flank wear due to the cooling effect of air and less amount of work material deposit on the tool. Furthermore, reduced tool wear has been found at 200 m min −1 in comparison to 150 m min −1 due to high speed with low feed results in reduced tool wear [50]. The fact that tool wear is mainly determined by the temperature generated at the cutting zone explains the ability of the RHVT MF strategy to reduce tool flank wear [51].…”
Section: Tool Wearmentioning
confidence: 99%